Conflict Transformation: Relinquishing or Maintaining Social Identity Among Former Loyalist Combatants in Northern Ireland. Issue 2 (19th October 2020) - Flack, Patrick; Ferguson, Neil
Abstract : This study explored the accounts of former loyalist combatants now involved in conflict transformation, preventing violent extremism and peace‐building work. To understand how former loyalist combatants negotiate their dramatic change in context and function, we analyzed accounts of peace building through thematic analysis. The themes demonstrated that conducting conflict transformation is expressively linked to former combatant identity. The themes also demonstrate that former combatants construct identity continuity by viewing their current transformative actions as an evolution of their militant activity during the Troubles. The article concludes on the implications of these identity maintenance strategies for former combatants and, more widely, what implications this has for other militants transitioning from conflict or extremism towards peace.